2011
DOI: 10.2147/ijn.s18347
|View full text |Cite
|
Sign up to set email alerts
|

Memecylon edule leaf extract mediated green synthesis of silver and gold nanoparticles

Abstract: We used an aqueous leaf extract of Memecylon edule (Melastomataceae) to synthesize silver and gold nanoparticles. To our knowledge, this is the first report where M. edule leaf broth was found to be a suitable plant source for the green synthesis of silver and gold nanoparticles. On treatment of aqueous solutions of silver nitrate and chloroauric acid with M. edule leaf extract, stable silver and gold nanoparticles were rapidly formed. The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(138 citation statements)
references
References 33 publications
11
126
0
1
Order By: Relevance
“…The extract was filtered and stored in an airtight container and protected from sunlight for further use. 37 …”
Section: Preparation Of Aqueous Extractmentioning
confidence: 99%
“…The extract was filtered and stored in an airtight container and protected from sunlight for further use. 37 …”
Section: Preparation Of Aqueous Extractmentioning
confidence: 99%
“…Our results are consistent with other studies on the stability of GNPs synthesized from plant compounds. 14,15 A key parameter in evaluating biocompatibility is centered on the evaluation of potential cytotoxicity of the materials. The in vitro cytotoxicity effect of nanomaterials is most often assessed from mitochondrial enzyme activity using tetrazolium salt (MTT assay), with respect to the untreated cell as a control.…”
Section: Stability and Cytotoxicity Of Gnpsmentioning
confidence: 99%
“…13 GNPs have been synthesized using phytochemicals from Terminalia chebula, Breynia rhamnoides, Memecylon edule, Cinnamomum verum, Macrotyloma uniflorum, Rosa hybrid, ginseng soybean and Aloe vera. [14][15][16][17][18] Furthermore, Vitis vinifera L. was used for the synthesis of silver nanoparticles. 19 These authors showed that phytochemicals in the plant show unique kinetic property to reduce gold salts to form GNPs.…”
Section: Introductionmentioning
confidence: 99%
“…This process opens up new opportunities in the recycling of wastes and could be useful in areas such as cosmetics, food or medicine. The latest research in this field focus on the synthesis of gold and silver nanoparticles with various plants: Medicago sativa (Bali & Harris, 2010;Gardea et al, 2002), Vigna radiata, Arachis hypogaea, Cyamopsis tetragonolobus, Zea mays , Pennisetum glaucum, Sorghum vulgare (Rajani et al, 2010), Brassica juncea (Bali & Harris, 2010;Beattie & Haverkamp, 2011) or extracts from B. juncea and M.sativa (Bali & Harris, 2010), Memecylon edule (Elavazhagan & Arunachalam, 2011) or Allium sativum L. (Ahamed et al, 2011). Depending on the nanoparticle's nature, specie of plant or tissue in which they are stored, metal nanoparticles of different shapes and sizes can be obtained.…”
Section: Particle Farmingmentioning
confidence: 99%